Mineral scales and deposits : scientific and technological approaches - Amjad, Zahid; Demadis, Konstantinos D. (Elsevier, 2015)
Mineral Scales and Deposits: Scientific and Technological Approaches presents, in an integrated way, the problem of scale deposits (precipitation/crystallization of sparingly-soluble salts) in aqueous systems, both industrial and biological. It covers several fundamental aspects, also offering an applications' perspective, with the ultimate goal of helping the reader better understand the underlying mechanisms of scale formation, while also assisting the user/reader to solve scale-related challenges. It is ideal for scientists/experts working in academia, offering a number of crystal growth topics with an emphasis on mechanistic details, prediction modules, and inhibition/dispersion chemistry, amongst others. In addition, technologists, consultants, plant managers, engineers, and designers working in industry will find a field-friendly overview of scale-related challenges and technological options for their mitigation.